In-Detoxification: Therapeutic architecture toward healing substance abuse - Gunkel, Tymon (Faculty of Engineering and the Built Environment, 2023)
This study explores rehabilitation by means of therapeutic architecture, to rehabilitate individuals from substance abuse and addiction. The study aims to understand how rehabilitation can benefit the community, facilitated by a community orientated program for individuals. The site used for the project is located within the Cape-Flats, in the town of Mitchells Plain. This project aims to study the concept, practice, and technologies behind creating a rehabilitation center that uses phenomenology and therapeutic design principles as its underpinning to create a therapeutic environment in the form of a rehabilitating center. The study aims to understand architectural means allowing a healthy relationship between the urban and the individual, encouraging and establishing respect for the community through program. The study is done as a response to the current social issues displayed in the Cape-flats and modern healthcare facilities whose design is based on the ability to function and house medical equipment rather than performing as an instrument of healing.